Characterization of the cytoplasmic chaperonin containing TCP-1 from the Antarctic fish Notothenia coriiceps. - Pucciarelli, Sandra; Parker, Sandra K; Detrich, H William; Melki, Ronald (Extremophiles, 2006)
International audience The cytoplasmic chaperonin containing TCP-1 (CCT) plays a critically important role in the folding and biogenesis of many cytoskeletal proteins, including tubulin and actin. For marine ectotherms, the chronically cold Southern Ocean (-2 to +2 degrees C) poses energetic challenges to protein folding, both at the level of substrate proteins and with respect to the chaperonin/chaperone folding system. Here we report the partial functional and structural characterization of CCT from an Antarctic notothenioid fish, Notothenia coriiceps. We find that the mechanism of folding by the Antarctic fish CCT differed from that of mammalian CCT: (1) the former complex was able to bind denatured beta-tubulin but (2) when reconstituted with rabbit Cofactor A, failed to release the protein to yield the tubulin/cofactor intermediate. Moreover, the amino acid sequences of the N. coriiceps CCT beta and theta chains contained residue substitutions in the equatorial, apical, and intermediate domains that would be expected to increase the flexibility of the subunits, thus facilitating function of the chaperonin in an energy poor environment. Our work contributes to the growing realization that protein function in cold-adapted organisms reflects a delicate balance between the necessity of structural flexibility for catalytic activity and the concomitant hazard of cold-induced denaturation.